2017
DOI: 10.1016/j.kint.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage density in early surveillance biopsies predicts future renal transplant function

Abstract: Inflammation impairs renal allograft survival but is difficult to quantify by eye at low densities. Here we measured leukocyte abundance in early surveillance biopsies by digital image analysis to test for a role of chemokine receptor genotypes and analyze the predictive value of leukocyte subsets to allograft function. In six-week surveillance biopsies, T-cell (CD3), B-cell (CD20), macrophage (CD68), and dendritic cell (CD209) densities were assessed in whole slide scans. Renal cortical CD3, CD20, and CD68 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 57 publications
(77 reference statements)
4
39
0
1
Order By: Relevance
“…This finding is consistent with previous observations emerging from protocol biopsies, 5,6,9,10 in keeping with a possible role of macrophages in promoting the activation and recruitment of myofibroblasts to areas of inflammation and eventually leading to fibrosis 11 and is consistent with a recent paper reporting that the macrophage-to-myofibroblast transition may contribute to interstitial fibrosis in both human and experimental chronic allograft injury. 12 Moreover, macrophage infiltration is also associated with poor long-term eGFR behavior in kidneys from deceased but not from living donors, thus confirming a potential role of early inflammation in the risk of subsequent CKD in KTRs after transplantation, and somewhat explaining the better outcome observed in KTRs receiving kidneys from living donors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous observations emerging from protocol biopsies, 5,6,9,10 in keeping with a possible role of macrophages in promoting the activation and recruitment of myofibroblasts to areas of inflammation and eventually leading to fibrosis 11 and is consistent with a recent paper reporting that the macrophage-to-myofibroblast transition may contribute to interstitial fibrosis in both human and experimental chronic allograft injury. 12 Moreover, macrophage infiltration is also associated with poor long-term eGFR behavior in kidneys from deceased but not from living donors, thus confirming a potential role of early inflammation in the risk of subsequent CKD in KTRs after transplantation, and somewhat explaining the better outcome observed in KTRs receiving kidneys from living donors.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous observations emerging from protocol biopsies, 5,6,9,10 Protocol kidney biopsies of KTRs showed that interstitial macrophage infiltration in the first post-transplant year was associated with the development of renal graft fibrosis. 6 This finding is in keeping with a possible role of macrophages in promoting the activation and recruitment of myofibroblasts to areas of inflammation and eventually leading to fibrosis 11 and is consistent with a recent paper reporting that the macrophage-to-myofibroblast transition may contribute to interstitial fibrosis in both human and experimental chronic allograft injury.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, this strategy may help us to understand and distinguish the inflammatory and profibrotic phases of inflammation and/or the activity of inflammation. To this end, multiplex immunohistochemistry is likely to be especially useful, as inflammatory cells are mixed in nature and vary throughout the rejection process [62][63][64]. Digital pathology has become increasingly popular in pathology practice, both in clinical biopsy diagnosis and in research.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, different phenotypic and molecular studies uncovered that the composition of the infiltrate may be significant. For example, the quantity of macrophages may be a predictive factor for kidney allograft loss . Moreover, both CD20 + B lymphocyte and CD68 + macrophage (but not CD3 + T lymphocyte) densities in early surveillance biopsies inversely correlate with estimated glomerular filtration rate 4 years after transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the quantity of macrophages may be a predictive factor for kidney allograft loss . Moreover, both CD20 + B lymphocyte and CD68 + macrophage (but not CD3 + T lymphocyte) densities in early surveillance biopsies inversely correlate with estimated glomerular filtration rate 4 years after transplantation . Consequently, the use of a panel of antibodies to determine the in situ immunopathologic component at the time of rejection diagnosis may be relevant.…”
Section: Introductionmentioning
confidence: 99%